PENGARUH CAPITAL INTENSITY DAN KONEKSI POLITIK TERHADAP TAX AVOIDANCE - Karina Hifnalisa (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Tax avoidance actions by taxpayers can occur for different interests between the government and taxpayers by exploiting loopholes in the tax law and several factors that influence it. The purpose of this study was to determine the impact of capital intensity and political connections on tax avoidance. The population used in this survey are state-owned companies listed on the Indonesia Stock Exchange from 2015 to 2018. The sample research technique used purposive sampling with the resulting sample of 14 companies. Descriptive statistical tests and simple linear regression by the IBM SPSS Statistics 20 program are used as the analysis method. The results show that capital intensity and political connections have a significant impact on tax avoidance for BUMN companies listed in IDX 2015-2018.